PENGARUH INFLASI, PDB, DER, ROE, NPM, GPM TERHADAP TINGKAT SEWA SUKUK IJARAH: Dibuat oleh Iftitah Nurul Azizah, Muhammad Yusuf, Yohani (Prodi Akuntansi FEB Universitas Muhammadiyah Pekajangan Pekalongan) - muhamad yusuf; Iftitah Nurul Azizh; Yohani - (Neraca, 2020)
The existence of sukuk ijarah which provide fix return more attractive to investors than sukuk mudharabah. According to the investors, the sukuk ijarah is considered quite prospective for the emitten’s intending to issue sukuk. The aim of this study is to find out the influence of inflation, PDB, DER, ROE, NPM, GPM to sukuk ijarah rental rate. The populations on this study were all companies listed on the Indonesian Stock Exchange and issued sukuk ijarah in 2013-2019 which report completely and published the financial reports. Purposive sampling method was used in this study. Samples that suitable with the criteria of this study were 5 companies. The method of analysis is multiple regression analysis in SPSS. The results indicate partially the inflation, PDB, DER, ROE, NPM, and GPM variables have no significant effect to sukuk ijarah rental rate. Meanwhile, the NPM variable has significant effect to sukuk ijarah rental rate. The study results simultancously show that the inflation, PDB, DER, ROE, NPM, GPM variables have significant effect to sukuk ijarah rental rate. Further research can add other variables such as ROA and debt to aset ratio. The sample used should also be more than the sample in this study and it is expected that the mudharabah Islamic bonds can be added as another object of the study. Keywords : inflation, PDB, DER, ROE, NPM, GPM, and sukuk ijarah rental rate